Simplifying
7y + 3 + 3y + -5 = 9y + 7
Reorder the terms:
3 + -5 + 7y + 3y = 9y + 7
Combine like terms: 3 + -5 = -2
-2 + 7y + 3y = 9y + 7
Combine like terms: 7y + 3y = 10y
-2 + 10y = 9y + 7
Reorder the terms:
-2 + 10y = 7 + 9y
Solving
-2 + 10y = 7 + 9y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-9y' to each side of the equation.
-2 + 10y + -9y = 7 + 9y + -9y
Combine like terms: 10y + -9y = 1y
-2 + 1y = 7 + 9y + -9y
Combine like terms: 9y + -9y = 0
-2 + 1y = 7 + 0
-2 + 1y = 7
Add '2' to each side of the equation.
-2 + 2 + 1y = 7 + 2
Combine like terms: -2 + 2 = 0
0 + 1y = 7 + 2
1y = 7 + 2
Combine like terms: 7 + 2 = 9
1y = 9
Divide each side by '1'.
y = 9
Simplifying
y = 9